Conventional Therapy vs Nitazoxanide Plus Omeprazole for the Eradication Of Helicobacter Pylori : A Randomized Control Trial - Rouf, Md Abdur; Sayeed, Abdullah Abu; Waez, Mohammad Shakeel; Hasan, Kazi Mohammad Abrar; Uddin, Mohammed Jashim; Ahmed, Ershad Uddin; Hoque, Md Gofranul (Journal of Chittagong Medical College Teachers' Association, 2016)
Helicobacter pylori has an important association with Peptic Ulcer Disease (PUD). Numerous trials have proved that eradication of Helicobacter pylori results in healing of PUD and a very low recurrence rate. Attempts at eradication in Bangladesh with different regimens showed poor results. In Bangladesh there is no study with regimen containing Nitazoxanide and Omeprazole that showed to be very effective in several trails in different countries. This study was conducted in the Medicine department, Chittagong Medical College Hospital, from December 2008 to November 2009 to evaluate the efficacy of Nitazoxanide and Omeprazole in the eradication of Helicobacter pylori in PUD patients of Bangladesh. 130 endoscopically proven PUD patients were enrolled in this study when rapid urease test gave positive result & randomized into two halves for comparison of treatment regimens. After six weeks endoscopy was done. Ulcer healing, rapid urease test negativity and absence of Helicobacter pylori in histology was considered as cure. Conventional group treated with Clarithromycin, Amoxicillin, Lansoprazole for 14 days showed cure rate of 80%, whereas nitazoxanide group showed 76% cure, the difference is not statistically significant. This study shows that two regimens are effective and comparable though newer regimen failed to show superiority over conventional treatment. JCMCTA 2016 ; 27 (1) : 33 - 39